EVALUATION OF THE FEDERAL AUDIT OFFICE ACCORDING TO THE ENABLERS STANDARDS OF THE EUROPEAN FOUNDATION FOR QUALITY MANAGEMENT MODEL EFQM - Aizdihar Jasim muhamad; Jasim Muhamad Hussein; Lect. Dr. Abdulmahdi Abdulhussain Idan Al-Mansouri (Scholars Digest Publishing, 2024)
Has become Supreme Audit Institutions and accounting plays a vital role in holding governments accountable for their management of public funds and to help ensure the transparency of this administration, which should be on these devices to organize and manage the operations and activities of their own over the way the effectiveness, in light of the global trend towards quality and organizational excellence, and the fact that devices Supreme financial Control and Accounting seek in all countries of the world to achieve the greatest possible efficiency and effectiveness in the performance of search, including access to the highest levels of quality and excellence, not only in the level of duties controls, but the overall institutional level, it was necessary for these devices from the adoption of practical management frameworks TQM help in determining the appropriate improvement activities that enable them to achieve excellent results as well as used as a tool to assess and evaluate the performance of the machine. So Find eat a specimen of the European Foundation for Quality Management (EFQM) framework represents the best practices for the application of the principles of total quality management, and focused research problem in the lack of adoption of devices supreme financial control model for assessing the level of business performance internationally recognized reflected negatively on determining the level of the performance in terms of the lack of clear strengths and weaknesses and opportunities for improvement and development should be strengthened by focusing on the relationships between people, processes and results, which will bring the development of resources and raise the quality of corporate performance, and therefore the reflection on the quality of audit work.The importance of research in two foremost importance that acquired the specimen European Foundation for Quality Management (EFQM), which provides a self-assessment tool using a detailed set of flexible standards on how and when to apply, and the second the importance of the role played by SAIs and the importance of undertaking the process of self-evaluation of its performance and find the quality of their work supervisory measurable indicators as well as determine the quality of performance checksum for each worker watchdog inside this device level. The research aims to shed light on the model of the European Foundation for Quality Management (EFQM) as a framework for the application of the principles. Was based on research into the premise of the President of the effect that the adoption of supreme financial control devices worldwide model for evaluating corporate performance represented Bonmozj European Foundation for Quality Management (EFQM) In light of the study of the research was to reach a set of conclusions, namely The model of the European Foundation for Quality Management framework to manage the performance of organizations through its standards and its activities as well as it provides an effective tool for self-assessment and institutional Keywords: evaluation, financial control, enabler criteria.